Methylation of BRCA1 promoter region is associated with unfavorable prognosis in women with early-stage breast cancer. - Nicholas C Hsu (Public Library of Science (PLoS), 2013)
BRCA1-associated breast cancers are associated with particular features such as early onset, poor histological differentiation, and hormone receptor negativity. Previous studies conducted in Taiwanese population showed that the mutation of BRCA1 gene does not play a significant role in the occurrence of breast cancer. The present study explored methylation of BRCA1 promoter and its relationship to clinical features and outcome in Taiwanese breast cancer patients. Tumor specimens from a cohort of 139 early-stage breast cancer patients were obtained during surgery before adjuvant treatment for DNA extraction. Methylation of BRCA1 promoter region was determined by methylation-specific PCR and the results were related to clinical features and outcome of patients using statistical analysis. Methylation of the BRCA1 promoter was detected in 78 (56%) of the 139 tumors. Chi-square analysis indicated that BRCA1 promoter methylation correlated significantly with triple-negative (ER-/PR-/HER2-) status of breast cancer patients (p = 0.041). The Kaplan-Meier method showed that BRCA1 promoter methylation was significantly associated with poor overall survival (p = 0.026) and disease-free survival (p = 0.001). Multivariate analysis which incorporated variables of patients' age, tumor size, grade, and lymph node metastasis revealed that BRCA1 promoter methylation was associated with overall survival (p = 0.027; hazard ratio, 16.38) and disease-free survival (p = 0.003; hazard ratio, 12.19) [corrected].Our findings underscore the clinical relevance of the methylation of BRCA1 promoter in Taiwanese patients with early-stage breast cancer.